AN EMPIRICAL ANALYSIS OF INVESTIGATING CHEF’S PERCEPTION TOWARDS FOOD PREPARATION PRACTICES IN ALL CLASSIFIED HOTELS OF ODISHA(INDIA) - Mohanty, Patitapaban (ASEAN Journal on Hospitality and Tourism, 2018)
This paper attempt to find out chef?s perceptions of food preparation practices in some of the well-known hotels in Odisha. The most pivotal question to be examined in this study is the day to day culinary practices in preparing the variety of foods in order to satisfy the taste buds of different guest staying and coming to the hotels in Odisha. Though modern-day hotels are emphasizing more on personalized services, such as luxury accommodations, lavish dining, intimate hospitality, but food preparation practices which are core function of the hotels have taken a back seat in Odisha. Hence in this context, it is the high time for the chefs and even the management to investigate the food preparation practices which comes in the back of the house operation (BOH), and the other aspects like food quality, safety, sanitation, hygiene, standardization, menu planning associated with it also to be scanned completely.